ARABIC SCHOOLS AND THE PROMOTION OF FUNDAMENTAL BRITISH VALUES: A COMMUNITY'S AMBITIONS FOR CONSENSUAL DIVERSITY. Issue 6 (1st November 2020) - Szczepek Reed, Beatrice; Davies, Ian; Said, Fatma; Bengsch, Géraldine; Sally, Jayme
ABSTRACT: This article explores the positioning of a sample of Arabic complementary language schools in the context of the UK government's discourse and promotion of so-called Fundamental British Values. While there is considerable social and political debate about radicalisation in Arab communities, teachers in the sample are deeply committed to a form of consensual diversity, both in their schools and their communities. They are also supportive of so-called British values, which they frame as universal values. In their promotion of these values as universal, there may be the potential for diasporic disconnect: the schools are striving for integration which may at times result in assimilationist positioning in the context of government pressure. However, their discourse is embedded in the highly charged political context in which Arabic schools operate and in which they position themselves as stakeholders in Arab communities. On the basis of the qualitative evidence reported here some of the government's ways of challenging radicalisation seems unwarranted in relation to Arabic complementary language schools.